GAGASAN PENDIDIKAN ANTIKORUPSI MELALUI PEMBELAJARAN MATEMATIKA SEKOLAH DASAR - Aisyah Anggraeni (Program Studi PGSD FKIP Universitas Bung Hatta, 2019)
This paper intends to contribute to supporting the anti-corruption movement by instilling anti-corruption attitudes to students through learning mathematics in elementary schools. It is undeniable, the corruption cases in Indonesia seem to be endless, increasingly widespread and unsettling the public. The rise of corruption cases in Indonesia certainly cannot be allowed to drag on, let alone be left alone. So, real efforts or actions are needed that can awaken all elements of society in this country to equally move against this bad culture. One way that can be done is through the world of education. In this case, an anti-corruption curriculum is needed as an effort to eradicate corruption through formal education. The idea of ​​an anti-corruption curriculum can be through mathematics, namely by emphasizing the cultivation of anti-corruption attitudes.